Life Quality of Pediatric Patient with Dengue Hemorrhagic Fever (DHF) Who Received Crystalloid and Colloid Fluid Treatment in PKU Muhammadiyah Hospital Yogyakarta - Nasriyah, Chotijatun; Perwitasari, Dyah Aryani; Kurniawan, Nurcholid Umam (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2019)
Dengue hemorrhagic fever (DHF) in the community can have an impact of panic, death, and reduced age of hope in the family. Research on the quality of life of DHF pediatric patient who got the treatment of crystalloid and colloid fluids has never been done before. The purpose of this study was to determine the quality of life of DHF pediatric patients who received crystalloids and colloids with PedsQL instruments. The study design was a cohort with block randomization. The inclusion criteria in this study were hospitalized DHF pediatric patients aged one month -18 years from February to May 2018. The exclusion criteria were DHF patients who came with referrals from other hospitals who had received fluid therapy. Research data include the length of stay (LOS) and quality of life score with the PedsQL questionnaire. The statistical analysis was using an independent t-test and the Mann Whitney test. The length of stay for the crystalloid group is five days longer than the colloid group, which is four days. From a total of 48 subjects studied, the score for the physical function of the crystalloid fluid group 84.54 ± 9.90 was higher than the colloid group of 77.58 ± 19.30 (p = 0.125). The emotional functions in the crystalloid group obtained a score of 81.88 ± 12.14 higher than the colloid group, i.e., 79.17 ± 18.5 (p = 0.552). The social function in the crystalloid group had a score of 92.08 ± 8.84 higher than the colloid group of 86.67 ± 13.96 (p = 0.232). The school functions in the crystalloid group had a score of 50.42 ± 33.68 higher than in the colloid group of 37.92 ± 36.62 (p = 0.225). The results of this study showed that the crystalloid group had a higher quality of life score compared to the colloid group, although it was not significant.